If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3y + -2x + -2 = 0 Reorder the terms: -2 + 3x + -2x + 3y = 0 Combine like terms: 3x + -2x = 1x -2 + 1x + 3y = 0 Solving -2 + 1x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 1x + 2 + 3y = 0 + 2 Reorder the terms: -2 + 2 + 1x + 3y = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 1x + 3y = 0 + 2 1x + 3y = 0 + 2 Combine like terms: 0 + 2 = 2 1x + 3y = 2 Add '-3y' to each side of the equation. 1x + 3y + -3y = 2 + -3y Combine like terms: 3y + -3y = 0 1x + 0 = 2 + -3y 1x = 2 + -3y Divide each side by '1'. x = 2 + -3y Simplifying x = 2 + -3y
| (2x-6)(9x+1)=0 | | 5x^4+2x^3=10x^7 | | x^2-3x=1.8 | | 9y^2+z^2=16 | | 4x+x+3x+8x= | | 3(2x-6)=2(6x-3) | | An=xy | | -144/=-16 | | 3.67-6.7x+1.11=22.2 | | -(6xy-10)+2(5xy+8)= | | 5x+6x-3x-5=51 | | (4x^3+4x^2-3x)(x^2-7)=0 | | 5+(3x-3)=3x-(8x-6) | | C-50=28 | | 23=u-10 | | x(3x+2)=8 | | 30x^2-1=5x^2-1 | | x4=1/10 | | 6/7s-5/6s=4/21 | | 15=c/5 | | M+7m+3m-6= | | 2cos^2(2x)-cos(x)=0 | | 2s^2+3s-1=0 | | x^4-y^4-3y^2+1=0 | | -16x^2+75x-51=0 | | -6z=15-7z | | 2cos^2(2x)-cos(2)=0 | | 2x-3(x+3)=23 | | 4k-8=5(k+7) | | 25,200/525 | | x+18-9x=27-6x-9 | | 27=w-35 |